Prevalence, demographics, and clinical characteristics of Latin American patients with spondyloarthritis (2021)
Large epidemiologic and clinical estimates of spondyloarthritis (SpA) in Latin America are not available. In this narrative review, our goal was to descriptively summarize the prevalence and features of SpA in Latin America, based on available small studies. A review of peer-reviewed literature identified 41 relevant publications. Of these, 11 (mostly based on Mexican data) estimated the prevalence of SpA and its subtypes, which varied from 0.28 to 0.9% (SpA), 0.02 to 0.8% (ankylosing spondylitis), 0.2 to 0.9% (axial SpA), and 0.004 to 0.08% (psoriatic arthritis). Demographic and/or clinical characteristics were reported in 31 of the 41 publications, deriving data from 3 multinational studies, as well as individual studies from Argentina, Brazil, Chile, Colombia, Costa Rica, Mexico, Peru, Uruguay, and Venezuela. Data relating to treatment, disease manifestations (articular and extra-articular), and comorbidities were summarized across the countries. Available data suggest that there is a variability in prevalence, manifestations, and comorbidities of SpA across Latin America. Basic epidemiologic and clinical data are required from several countries not currently represented. Data relating to current treatment approaches, patient outcomes, and socioeconomic impact within this large geographic region are also needed.